2009
DOI: 10.1159/000228839
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Suicidality and Clusters of Hungarian Adolescent Outpatients Suffering from Suicidal Behaviour

Abstract: Background: The aim of the study was to reveal the background dimensions of suicidal behaviour (SB) and to identify clusters of Hungarian adolescent outpatients suffering from suicidality by means of the following correlates of SB: depression, inadequate conflict-solving methods, dysfunctional attitudes, maladaptive coping, help-seeking strategies and negative life events. Sampling and Methods: A self-report test battery was completed by every consecutive new adolescent outpatient from a representative patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 167 publications
1
3
1
Order By: Relevance
“…As for the intensity of NLEs, Nisikawa et al (2018) conclude that timing and intensity are associated with current symptoms of depression. Contrary to Dinya et al (2009) study on child psychiatric centers in Hungary concluding that adolescents who experienced a high number of negative life events and who were more heavily impacted by negative life events had the most maladaptive and risky ways of coping, our results shows that only low and moderate intensity events are associated to heighten anxiety displaying. But this conflicting result is explained by the nature of our measurement of intensity that we addressed in the Limits section.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As for the intensity of NLEs, Nisikawa et al (2018) conclude that timing and intensity are associated with current symptoms of depression. Contrary to Dinya et al (2009) study on child psychiatric centers in Hungary concluding that adolescents who experienced a high number of negative life events and who were more heavily impacted by negative life events had the most maladaptive and risky ways of coping, our results shows that only low and moderate intensity events are associated to heighten anxiety displaying. But this conflicting result is explained by the nature of our measurement of intensity that we addressed in the Limits section.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, our results show that exposure to NLEs are important to consider when discussing and understanding the occurrence of mental health problems among Romanian adolescents, thus contributing to the existing literature. Regarding the association between NLEs and internalizing problems and in line with other studies (Grant et al, 2004, 2014; Raknes et al, 2017b), our results showed that those adolescents who reported experiencing specific negative events also reported more depressive and anxiety symptoms, thus, supporting the claim that the occurrence of adversities is a risk factor for negative mental health outcomes Braboy Jackson & Finney, 2002; Dinya et al, 2009; Dovran et al, 2019; Măirean and Diaconu–Gherasim, 2018). Proximity of NLEs had a little effect on reported depression, but it had a greater impact on anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…and Cohen (1985a) reported that the most com mon negative life event was an increase in arguing with parents (34%), followed by breaking up with a boyfriend/girlfriend (33%), and breaking up with a close friend (20%). Since then, the JHLES has been used in many studies with adolescents and children (Brown & Fite, 2016;Dinya et al, 2009;Ge et al, 2006;King et al, 2017;Lasgaard et al, 2016;Swearingen & Cohen, 1985b).…”
Section: Negative Life Eventsmentioning
confidence: 99%
“…Systematic reviews of empirical studies regarding typologies of suicide and suicidal behaviors have been conducted (Arensman & Kerkhof, ; Wolodzko & Kokoszka, ). Included in these reviews are several studies utilizing cluster analyses as a statistical method to describe data collected via psychological autopsy (O'Connor et al., ), personality inventories (Ellis, Rudd, Rajab, & Wehrly, ; Engstrom, Alling, Gustavsson, Oreland, & Traskman‐Bendz, ; Rudd, Ellis, Rajab, & Wehrly, ), clinical inventories (Chen et al., ; Dinya et al., ; Lopez‐Castroman, Nogue, Guillaume, Picot, & Courtet, ; Rapeli & Botega, ; Steer, Beck, Brown, & Beck, ), or general population surveys (Flannery, Sneed, & Marsh, ). However, many of the studies included in these reviews are restricted to characteristics of suicide attempts, and the results have questionable generalizability to those who actually die by suicide.…”
mentioning
confidence: 99%
“…Despite established risk and protective factors, there is much diversity in how and why people die by suicide (Bardon, Cote, & Mishara, 2016;Barzilay & Apter, 2014;Chen et al, 2007;Henderson & Williams, 1974;Logan, Hall, & Karch, 2011;O'Connor, Sheehy, & O'Connor, 1999;Sinyor, Schaffer, & Streiner, 2014;Wold, 1971). In suicide research, typologies, or distinct and stable groups, have been proposed to classify cases based on societal (Durkheim, 1951), psychological (Baechler, 1979;Menninger, 1938;O'Connor et al, 2012), and relational factors (Leonard, 1967), and on the basis of human needs or motives (Mintz, 1968;Shneidman, 1968Shneidman, , 1980. Certain core themes emerge repeatedly within the literature, including escape, aggression, intra-psychic pain, and relational concerns.…”
mentioning
confidence: 99%